Ceutorhynchus-Studien (Coleoptera: Curculionidae). - Dieckmann, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1971)
Of the genus Ceutorhynchus Germar, the groups C. rugulosus- and C. chalybaeus are revised. Keys to the species of these three groups are presented, and data on their biology and distribution are given. Two new species are described, C. insularis spec. nov. from the Vestmanna Iceland and C. franzi spec. nov. from the Alps.Nomenclatural Actsfranzi Dieckmann, 1971 (Ceutorhynchus), spec. n.gallicus Gyllenhal, 1837 (Ceutorhynchus), Lectotype now a synonym of Ceutorhynchus rugulosus (Herbst, 1795)henschi Schultze, 1903 (Ceutorhynchus), syn. n. of Ceutorhynchus erysimi (Fabricius, 1787)insularis Dieckmann, 1971 (Ceutorhynchus), spec. n.micros Schultze, 1896 (Ceutorhynchus), syn. n. of Ceutorhynchus contractus (Marsham, 1802)rubiginosus Schultze, 1896 (Ceutorhynchus), syn. n. of Ceutorhynchus rugulosus (Herbst, 1795)ruebsaameni Kolbe, 1900 (Ceutorhynchus), syn. n. of Ceutorhynchus leprieuri Brisout, 1881scutellatus Stephens, 1831 (Ceutorhynchus), syn. n. of Ceutorhynchus uniguttatus (Marsham, 1802)